Técnicas modernas y vanguardistas para rellenos de bombonería con sabores y productos ecuatorianos - Juiña Luguaña, Darío Alexander (2018)
Ecuador has a very good quality cocoa Ecuador has a very good quality of cocoa, which is considered one of the best to extract a chocolate of good flavor and aroma, which stands out on other varieties of cocoa around the world. You must have a lot of control in the process, always taking care of applying good techniques, controlling the temperatures, and storage of these products to obtain a good quality chocolate and it has to have a good period to consume. Ecuador has a wide gastronomy, thanks to the wide variety of ingredients, such as herbs, spices, fruits, which help to highlight the flavors, with which it can easily be adapted and combined with chocolate to create a wide variety of chocolates with own flavors and unique of our Ecuadorian land, not only looking for sweet combinations, but also adapt salty flavors. Through different techniques and types of fillings that exist, it was possible to determine which are the best to have a good combination and harmony in terms of flavors, also combining different textures in a single chocolate, thus creating an experience to taste each chocolate.